Expediting the Irksome - the Cortical Approach: A Case report - Acharya, Pujan; Saimbi, Charanjeet Singh; Adhikari, Khushbu; Kumar, Bikash; Niure, Sita (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Corticotomy assisted orthodontic treatment is a promising interdisciplinary approach, which has offered solution to many limitations in the orthodontic therapy. The procedure involves the alveolar decortication in the form of cortical grooves and perforations performed around the teeth that are to be moved. In this case report, a 17 year old male under fixed orthodontic therapy with a complaint of delayed protraction of mandibular second molars underwent corticotomy procedure. The decortication was done followed by elevation of buccal and lingual flaps. After 2 weeks of the surgical procedure, orthodontic tooth movement was initiated.